Monetary transmission mechanism of the housing market in Korea : A VECM approach - Chua, Chia Yei (2013)
The 2007 US subprime crisis had demonstrated that the impact of the housing market could be far-reaching. Most significantly, the catastrophe demonstrated that the housing sector forms an integral part of an economy and could definitely affect the economy drastically. In this paper, we investigate whether the monetary policy provides a means to remedy these variations in the housing market. This paper wishes to focus on the immediate East Asia region and, thus, finds that South Korea provides the most complete data set. Hence, it is chosen as the representative country to examine the housing market and monetary policy interactions. Data on the industrial production index, consumer price index, deposit rates and housing market prices are collected for the post-Asian financial crisis period to pre-US subprime crisis period. A Vector Error-Correction model is estimated to model the data. Then, the corresponding structural form is utilized to compute the Impulse Response Function following an interest rate shock. The Forecast Error Variance Decompositions of the different factors are also provided as supplementary evidence. Our results demonstrate that, indeed, monetary policy does offer a mean to rectify instabilities in the housing market. Furthermore, its effect are relatively short-term and has limited effect on output, these add to the appeal of using it as an adjustment policy.